2004
DOI: 10.1590/s1516-89132004000200005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile to antimicrobials of Salmonella spp. isolated from human infections

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
2
0
3
Order By: Relevance
“…Similar to this study, Liebana et al (2001Liebana et al ( , 2002and Tamada et al (2001) reported the isolation of S. Mbandaka, S. Montevideo and S. Livingstone from animal sources. The findings of Delicato et al (2004) and of Fernandez et al (2003) were also comparable to our results. They reported the isolation of S. Enteritidis, S. Infantis and S. Typhimurium from human faeces.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to this study, Liebana et al (2001Liebana et al ( , 2002and Tamada et al (2001) reported the isolation of S. Mbandaka, S. Montevideo and S. Livingstone from animal sources. The findings of Delicato et al (2004) and of Fernandez et al (2003) were also comparable to our results. They reported the isolation of S. Enteritidis, S. Infantis and S. Typhimurium from human faeces.…”
Section: Discussionsupporting
confidence: 91%
“…Glostrup in canaries. However, this serovar was isolated from poultry slaughterhouses [31], water from poultry facilities [32], captive reptiles [33], and human fecal samples [34]. Furthermore, it was reported that the family dog could be implicated as source of a human S. ser.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao sorovar Salmonella Typhimurium, isolado apenas em fígados condenados, observa-se que uma cepa apresentou resistência a quatro antimicrobianos, caracterizando multirresistência 24,25 , realidade de grande preocupação para o estudo epidemiológico, em todo o mundo, deste sorotipo atualmente considerado como emergente, seja proveniente de isolamento de alimentos ou infecções humanas. A outra cepa de Salmonella Typhimurium foi sensível a todos os antimicrobianos testados.…”
Section: Antimicrobianounclassified